GLP-1 is both anxiogenic and antidepressant; divergent effects of acute and chronic GLP-1 on emotionality. (March 2016) - Anderberg, Rozita H; Richard, Jennifer E; Hansson, Caroline; Nissbrandt, Hans; Bergquist, Filip; Skibicka, Karolina P.
Highlights: Only acute GLP-1 or clinically used analog, Exendin-4, induce anxiety-like behavior. Dorsal raphe GLP-1 receptor stimulation is sufficient to induce anxiety-like behavior. Acute central GLP-1 receptor stimulation alters serotonin signaling in the amygdala. Chronic administration of Exendin-4 reduces depression-like behavior. Abstract: Glucagon-like peptide 1 (GLP-1), produced in the intestine and hindbrain, is known for its glucoregulatory and appetite suppressing effects. GLP-1 agonists are in clinical use for treatment of type 2 diabetes and obesity. GLP-1, however, may also affect brain areas associated with emotionality regulation. Here we aimed to characterize acute and chronic impact of GLP-1 on anxiety and depression-like behavior. Rats were subjected to anxiety and depression behavior tests following acute or chronic intracerebroventricular or intra-dorsal raphe (DR) application of GLP-1 receptor agonists. Serotonin or serotonin-related genes were also measured in the amygdala, DR and the hippocampus. We demonstrate that both GLP-1 and its long lasting analog, Exendin-4, induce anxiety-like behavior in three rodent tests of this behavior: black and white box, elevated plus maze and open field test when acutely administered intraperitoneally, into the lateral ventricle, or directly into the DR. Acute central GLP-1 receptor stimulation also altered serotonin signaling in the amygdala. In contrast, chronic central administration of Exendin-4 did not alter anxiety-like behavior but significantly reduced depression-like behavior in the forced swim test. Importantly, this positive effect of Exendin-4 was not due to significant body weight loss and reduced food intake, since rats pair-fed to Exendin-4 rats did not show altered mood. Collectively we show a striking impact of central GLP-1 on emotionality and the amygdala serotonin signaling that is divergent under acute versus chronic GLP-1 activation conditions. We also find a novel role for the DR GLP-1 receptors in regulation of behavior. These results may have direct relevance to the clinic, and indicate that Exendin-4 may be especially useful for obese patients manifesting with comorbid depression.